Obremenjenost zraka s cvetnim prahom - Kofol-Seliger, Andreja (Naše okolje, 2023)
The pollen measurement in May 2023 was performed in Izola, Ljubljana, Lendava, and Maribor. The article describes the situation on the measurement sites in May; an outlook for July is also included.
Keywords: alergeni; alergije; alergijske reakcije; cvetni prah